Clinical Features of Parosmia Associated With COVID‐19 Infection. Issue 3 (13th December 2021) - Lerner, David K.; Garvey, Katherine L.; Arrighi‐Allisan, Annie E.; Filimonov, Andrey; Filip, Peter; Shah, Janki; Tweel, Benjamin; Del Signore, Anthony; Schaberg, Madeleine; Colley, Patrick; Govindaraj, Satish; Iloreta, Alfred Marc
Abstract : Objective: To characterize the clinical features, risk factors, symptom time‐course, and quality of life implications for parosmia among coronavirus disease (COVID)‐related olfactory dysfunction patients. Methods: Individuals with olfactory dysfunction associated with laboratory‐confirmed or clinically suspected COVID‐19 infection were recruited from otolaryngology and primary care practices over a period from August 2020 to March 2021. Participants completed olfactory dysfunction and quality of life surveys. Results: A total of 148 (64.1%) of 231 respondents reported parosmia at some point. Parosmia developed within 1 week of any COVID‐19 symptom onset in 25.4% of respondents, but more than 1 month after symptom onset in 43.4% of respondents. Parosmia was associated with significantly better quantitative olfactory scores on Brief Smell Identification Test (8.7 vs. 7.5, P  = .006), but demonstrated worse quality of life scores, including modified brief Questionnaire of Olfactory Dysfunction—Negative Statements and Sino‐Nasal Outcome Test‐22 scores (12.1 vs. 8.5, P  < .001; 26.2 vs. 23.2, P  = .113). Participants who developed parosmia at any point were significantly younger and less likely to have history of chronic sinusitis than those who did not develop parosmia (40.2 vs. 44.9 years, P  = .007; 7.2% vs. 0.7%, P  = .006). Conclusion: COVID‐19‐associated olfactory dysfunction is frequently linked with development of parosmia, which often presents either at onset of smell loss or in a delayed fashion. Despite better quantitative olfactory scores, respondents with parosmia report decreased quality of life. A majority of respondents with persistent parosmia have sought treatment. Level of Evidence: 3 Laryngoscope, 132:633–639, 2022